2007
DOI: 10.1590/s0004-282x2007000500005
|View full text |Cite
|
Sign up to set email alerts
|

Is preoperative occupation related to long-term pain in patients operated for lumbar disc herniation?

Abstract: -Lumbar disc herniation (LDH) is a common cause of back and sciatic pain. When clinical treatment fails, surgery may be indicated in selected patients. Although surgery is effective in most cases, some of these patients may have a poor outcome. Different factors may influence these results and poor adaptation at work is one well-known cause of treatment failure. This study examines 350 patients on longterm follow-up after surgery for first-time LDH. The relationship was analyzed between occupation before surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…15 Also, housekeeping duties may have a negative effect on RTW among women. 16 Similar to other studies, 9,17 we found that a lower educational level is related to lower likelihood of RTW. Moreover, it has been shown that in…”
Section: Discussionsupporting
confidence: 85%
“…15 Also, housekeeping duties may have a negative effect on RTW among women. 16 Similar to other studies, 9,17 we found that a lower educational level is related to lower likelihood of RTW. Moreover, it has been shown that in…”
Section: Discussionsupporting
confidence: 85%
“…Patients who fail to recover from sciatic pain are at risk to develop chronic pain syndromes, which emphasizes the importance of identifying factors that can predict the outcome, both regarding short-and long-term results. Therefore, possible predictive factors for the surgical outcome have been studied, factor as age [10], sex [11], duration of leg pain [12], time to surgery [13], working status [14], type and level of disc herniation [4,15,16] and psychosocial factors [17,18].…”
Section: Introductionmentioning
confidence: 99%